Odpowiedź :
Mianownik musi być różny od zera.
2.
[tex]a) \ f(x) = \frac{x+1}{2}\\\\D = R[/tex]
[tex]b) \ f(x) = \frac{x-2}{x+1}\\\\x+1 \neq 0\\x \neq -1\\\\D = R \setminus\{-1\}[/tex]
[tex]c) \ f(x) = \frac{x^{2}}{x} + \frac{3}{x-7}\\\\x \neq 0 \ \ \wedge \ \ x \neq 7\\\\D = R \setminus\{0,7\}[/tex]
[tex]d) \ f(x) = \frac{3+x}{x^{2}+1}\\\\x^{2}+1 > 0 \ - dla \ kazdego \ x\\\\D = R[/tex]
[tex]e) \ f(x) = \frac{5x}{(x+2)(x-4)}\\\\x+2 \neq 0 \ \ \wedge \ \ x-4\neq 0\\x \neq -2 \ \ \wedge \ \ x \neq 4\\\\D = R \setminus\{-2,4\}[/tex]
[tex]f) \ f(x) = \frac{4}{x+9} + \frac{10}{x^{2}-3}\\\\x+9 \neq 0 \ \ \wedge \ \ (x+\sqrt{3})(x-\sqrt{3}) \neq 0\\\\x \neq -9 \ \ \wedge \ \ x \neq -\sqrt{3} \ \ \wedge \ \ x \neq \sqrt{3}\\\\D = R \setminus\{-9, -\sqrt{3}, \sqrt{3}\}[/tex]